Living with Inflammatory Bowel Disease: A Crohn's and Colitis Canada Survey. Issue 2 (2015) - Becker, Helen M; Grigat, Daniel; Ghosh, Subrata; Kaplan, Gilaad G; Dieleman, Levinus; Wine, Eytan; Fedorak, Richard N; Fernandes, Aida; Panaccione, Remo; Barkema, Herman W
Abstract : BACKGROUND: Despite improvements in therapies for inflammatory bowel diseases (IBDs), patient quality of life continues to be significantly impacted. OBJECTIVE: To assess the impact of IBD on patients and families with regard to leisure, relationships, mental well-being and financial security, and to evaluate the quality and availability of IBD information. METHODS: An online survey was advertised on the Crohn's and Colitis Canada website, and at gastroenterology clinics at the University of Alberta Hospital (Edmonton, Alberta) and University of Calgary Hospital (Calgary, Alberta). RESULTS: The survey was completed by 281 IBD patients and 32 family members. Among respondents with IBD, 64% reported a significant or major impact on leisure activities, 52% a significant or major impact on interpersonal relationships, 40% a significant or major impact on financial security, and 28% a significant or major impact on planning to start a family. Patient information needs emphasized understanding disease progression (84%) and extraintestinal symptoms (82%). There was a strong interest in support systems such as health care insurance (70%) and alternative therapies (66%). The most common source of information for patients was their gastroenterologist (70%); however, most (70%) patients preferred to obtain their information from the Crohn's and Colitis Canada website. CONCLUSIONS: The impact of IBD on interpersonal relationships and leisure activities was significant among IBD patients and their families. Understanding the disease, but also alternative treatment options, was of high interest. Currently, there is a discrepancy between interest in information topics and their availability. Respondents reported a strong desire to obtain information regarding disease progression, especially extraintestinal symptoms.